Teoria e história da liberdade em Leonardo Bruni - Baggioni, Laurent (Discurso, 2022)
This article sheds light on the semantic fluctuations of the term “freedom” in the work of Leonardo Bruni, seeking to nuance its apprehension by the tradition of political thought known as neo-republicanism. Based on the conceptual and stylistic analysis of several central passages in the work of the Florentine author, the article aims to return to the uses and meanings of the word “freedom” in Bruni, questioning the relations between its “theoretical” use and its historical or narrative use.